Effect of nonsurgical periodontal therapy on interleukin-35 level in gingival crevicular fluid - Ashwini Jadhav; Surekha Ramrao Rathod; Abhay P Kolte; Palak Kasliwal (SRM Journal of Research in Dental Sciences, 2023)
Background: Clinical attachment level (CAL), alveolar bone loss, and periodontal pockets constitute the major signs of periodontitis. The interaction between the host and the bacteria that forms a biofilm on the tooth surface is one of the major etiologies of periodontal disorders. Aim: The aim of this study was to assess interleukin-35 (IL-35) levels pre and post nonsurgical periodontal therapy (NSPT) in healthy individuals and gingivitis and periodontitis patients. Materials and Methods: IL-35 level in gingival crevicular fluid (GCF) and clinical parameters were assessed in 60 individuals. Biochemical analysis was done by enzyme-linked immunosorbent assay. Individuals in Group I were in good health; those in Groups II and III had gingivitis and periodontitis, respectively. Study individuals were evaluated at baseline and 3 months after NSPT. Results: Group III differed from Group II in that it had higher CAL (7.60), plaque index (2.8929), and periodontal probing depth (5.8500 mm) values, as well as lower papillary bleeding index (2.1170) and gingival index (2.1085) values. The concentrations of IL-35 in GCF varied among the groups, with Group III having the lowest concentrations and rising gradually to Groups II and I. In addition, from baseline to 3 months, the IL-35 levels in GCF significantly decreased in both Groups II and III. The results show that Groups II and III have lower GCF levels of IL-35 than Group I, suggesting that IL-35 is a major factor in the development of periodontal diseases. Conclusion: Group I had considerably greater GCF IL-35 values than Group II and III both before and after NSPT.